(3GdefJbi ef JGQjN GdESdGe ddPgHis - (3CMeO Hf GdedG eMeO Hf Ydj Hf CMeO GdTGaYjs; (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3ef SfI (B91(3g` s
(3BNQgG (B:s
(3Edi SfI (B240(3g` s
(3ef SfI (B91 -(3SfI (B240(3g`s
(3hgj ecedI HNW BNQs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
Keywords: (3GdJGQjNs